Case Report: Dental treatment under general anesthesia and dental management of a child with congenital ichthyosis - Ryoko Hino; Yuta Chiba; Yuriko Maruya; Manami Tadano; Shinji Otake; Seira Hoshikawa; Yoji Sasahara; Kan Saito (Frontiers Media S.A., 2024)
Congenital ichthyosis is a disease in which the stratum corneum on the surface of the skin becomes thick from the time of the fetus and the barrier function of the skin is impaired. Congenital ichthyosis is a genetic disorder that causes ectodermal abnormalities and sometimes affects skin, nails, and tooth enamel. Therefore, some patients require special care in their daily life and during dental treatments. Here, the authors report a case of congenital ichthyosis that developed into severe dental caries at two years and nine months of age. The authors performed whole-exome sequencing in his peripheral blood and found that the patient had compound heterozygous mutations in ALOX12B gene (c.159C>G and c.1579G>A), which is responsible for autosomal recessive congenital ichthyosis-2 (MIM#2421000). Mutation of c.159C>G is a nonsense mutation that has never been reported, therefore novel symptoms might have found. The patients exhibited severe caries by hypoplastic teeth. Here, the authors report the treatment of dental caries in a patient with congenital ichthyosis under general anesthesia and its oral management until mixed dentition.